Bycatch mortality of endangered coho salmon: impacts, solutions, and aboriginal perspectives. Issue 7 (1st October 2014) - Raby, Graham D.; Donaldson, Michael R.; Nguyen, Vivian M.; Taylor, Mark K.; Sopinka, Natalie M.; Cook, Katrina V.; Patterson, David A.; Robichaud, David; Hinch, Scott G.; Cooke, Steven J.
Abstract : We used biotelemetry and human dimensions surveys to explore potential solutions to migration mortality of an endangered population of coho salmon caught as bycatch in an aboriginal beach seine fishery. From 2009 to 2011, 182 wild coho salmon caught as bycatch in the lower Fraser River (Canada) were radio‐tagged and tracked as they attempted to complete their migrations to natal spawning areas over 300 km upstream. Failure to survive to reach terminal radio receiving stations averaged 39% over three years. This mortality estimate is low compared to those obtained from telemetry studies on other salmon fisheries in the Fraser River. However, this value is markedly higher than the mortality estimate currently used to manage the fishery's impact. It is also in contrast to the perceptions of the majority of aboriginal fishers, who did not think survival of coho salmon is affected by capture and release from their fishery. Increased probability of survival was associated with lower reflex impairment, which is consistent with previous findings. Reflex impairment was positively correlated with entanglement time, suggesting that greater efforts by the fishers to release bycatch from their nets quickly would minimize post‐release mortality. Survey responses by aboriginal fishers also suggested that they are receptive to employing new bycatch handling methods if they are shown to increase post‐release survival. However, attempts to facilitate revival of a subset of captured fish using cylindrical in‐river recovery bags did not improve migration success. Fisheries managers could use the new information from this study to better quantify impacts and evaluate different harvest options. Since aboriginal fishers were receptive to using alternate handling methods, efforts to improve knowledge on minimizing reflex impairment through reductions in handling time could help increase bycatch survival. Such a direct integration of social science and applied ecology is a novel approach to understanding conservation issues that can better inform meaningful actions to promote species recovery.